Skull ontogeny of Lycalopex culpaeus (Carnivora: Canidae): description of cranial traits and craniofacial sutures - Segura Gago, Alda Valentina (2013)
Ontogenetic changes in the skull of Lycalopex culpaeus were studied in relation to feeding function and performance at different age classes. Most cranial changes occurred in the orbitotemporal region and consisted of the visible appearance of structures that were later found to be absent in juveniles. These changes were related to the development of the adult skull in order to capture, kill, and process prey. In general, fusion occurred earlier in neurocranial sutures than in the splachnocranium, although rostral sutures never became fused. The cranial sutures of culpeo are conservative, displaying few changes in suture type but some in suture fusion sequence. These modifications occur during the first year, from the late juvenile stages, when individuals are similar to adults in general appearance and body size as well as in skull size. However, it was noted that basicranial synchondroses became fused in the adult stages, indicating that longitudinal growth could extend until this latter time. This could be indicative not only of size change in adult specimens but also of shape change.